Incidence and pattern of overuse and traumatic injuries among adolescent elite athletes in canoe sprint, handball, and triathlon - Cassel, M.; Schomöller, A.; Risch, L.; Engel, T.; Joost, T.; Stoll, J.; Beckendorf, C.; Mayer, F. (Sportverletzung Sportschaden, 2025)
Abstract